Studying Some of Mechanical and Thermal Properties of Al-SiC composites - Abdul-Ameer, Zehraa N (Al-Nahrain Journal of Science, 2013)
In this research two groups of composites have been made : the first group has been sintered. For (1 hour) the second group has been sintered for ( 2 hours) and they were heat treated at 550oC. Mechanical properties such as wear rate ,impact strength from and thermal conductivity for different compositions of SIC% and they were tested .from the results one can see that increasing the SiC% composition increased the thermal conductivity to 150 W/mK for samples sintered (2hours) and 150 W/mK for (1hour)sintering while impact strength have the value of 9.8 J and 9.5 J for samples sintered for 1 and 2 hours respectively, decreasing in wear rate value with the increase of SiC composition to 1*exp(-8) rather than o.5 *exp(-8) gm/cm for 1 and 2 hours of sintering respectivel